(3QSGdI aj gd JbOe GdahGcg Ydi GdWYGe Ce dGs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd GdMcje eMeO Hf RcQjG GdQGRi GNJa GdCWHGA ai JbOje GdahGcg bHd GdGWYeI hGdCWYeI bHd GdahGcg s
(3BNQgG (B:s
(3eG jMJGL Edjg ef Pdc Ydi MSH GdbGfhf GdPi bOefGg JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs